2013
DOI: 10.1039/c2sc21654j
|View full text |Cite
|
Sign up to set email alerts
|

Chemical transformations of a crystalline coordination polymer: a multi-stage solid–vapour reaction manifold

Abstract: In its crystal structure the one-dimensional coordination polymer [Ag 4 (O 2 C(CF 2 ) 2 CF 3 ) 4 (TMP) 3 ] n (1) (TMP ¼ 2,3,5,6-tetramethylpyrazine) adopts a zig-zag arrangement in which pairs of silver(I) centres bridged by two fluorocarboxylate ligands are linked alternately via one or two neutral TMP ligands. This material can reversibly absorb/desorb small alcohols (ROH) in single-crystal-to-single-crystal transformations, despite the lack of porosity in the crystals, to yield a related material of formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 106 publications
3
36
1
Order By: Relevance
“…It is important to note that no loss of TMP ligands was detected, which may suggest that there is no facile pathway for escape of the ligand. This contrasts with our observations for monocarboxylate-containing material [Ag 4 (O 2 CCF 2 CF 2 CF 3 ) 4 (TMP) 3 ], which upon heating loses TMP and rearranges to give [Ag 4 (O 2 CCF 2 CF 2 CF 3 ) 4 (TMP) 2 ] [19,20]. Structure determination of the intermediate material would shed light on the mechanism of the solid-state rearrangement, which requires considerable reorganization of metal–ligand bonding, and again highlights the flexibility and propensity for breaking and formation of coordination bonds in the crystalline solid state.…”
Section: Discussioncontrasting
confidence: 99%
“…It is important to note that no loss of TMP ligands was detected, which may suggest that there is no facile pathway for escape of the ligand. This contrasts with our observations for monocarboxylate-containing material [Ag 4 (O 2 CCF 2 CF 2 CF 3 ) 4 (TMP) 3 ], which upon heating loses TMP and rearranges to give [Ag 4 (O 2 CCF 2 CF 2 CF 3 ) 4 (TMP) 2 ] [19,20]. Structure determination of the intermediate material would shed light on the mechanism of the solid-state rearrangement, which requires considerable reorganization of metal–ligand bonding, and again highlights the flexibility and propensity for breaking and formation of coordination bonds in the crystalline solid state.…”
Section: Discussioncontrasting
confidence: 99%
“…Porous coordination polymers (PCPs), more commonly known as metal-organic frameworks (MOFs), have enjoyed particular attention due to their potential application in gas sorption and separation (Li et al, 1999;Zhang & Chen, 2009;Sumida et al, 2009;D'Alessandro et al, 2010;Burd et al, 2012;FitzGerald et al, 2013;Carrington et al, 2014), heterogeneous catalysis (Gomez-Lor et al, 2002;Wu et al, 2005;Lee et al, 2009;Li et al, 2009Li et al, , 2014 and novel optical and magnetic properties (Evans & Lin, 2002;Zhou et al, 2013;Baldoví et al, 2014;Wang et al, 2014). The post-synthetic modification (PSM) of coordination polymers and PCPs has only more recently been the focus of more detailed work (Ingleson et al, 2008;Tanabe et al, 2008;Wang & Cohen, 2009;Nguyen & Cohen, 2010;Vermeulen et al, 2013;Zheng et al, 2013;Li et al, 2013), facilitating the multi-step synthesis of materials (Ingleson et al, 2008;Tanabe et al, 2008;Wang & Cohen, 2009;Nguyen & Cohen, 2010;Vermeulen et al, 2013;Zheng et al, 2013;Li et al, 2013;Libri et al, 2008;Vitó rica-Yrezá bal et al, 2013), stereo-or regio-selective transformation of ligands (Jones & Bauer, 2009) or the modification of solid-state properties of porous materials (Wang & Cohen, 2009;Nguyen & Cohen, 2010). The flexibility an...…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our own work has examined solid-gas and solid-vapour reactions involving molecular crystals of coordination compounds that reversibly react with HCl and HBr gases (Mínguez Espallargas et al, 2006, 2007Vitó rica-Yrezá bal et al, 2011), and coordination polymers that reversibly take up and release small alcohol molecules (Libri et al, 2008;Vitó rica-Yrezá bal et al, 2013), in each case requiring changes in metal coordination environments that are accompanied by structural changes and changes in intermolecular interactions (hydrogen bonding and/or halogen bonding). The present study builds upon earlier work that introduced a variety of networks formed by combining silver(I) perfluorocarboxylates with neutral ditopic ligands such as pyrazines and in particular emphasized the silver carboxylate dimer, Ag 2 (O 2 CR) 2 , as a secondary building unit (SBU) that can be linked by ditopic ligands into coordination polymers ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…
Examples from our work on coordination polymers and network materials (e.g. MOFs) will be used to illustrate the flexibility in these crystalline solids that enables chemical transformations to take place [1][2][3][4]. Two classes of compounds will be considered.
…”
mentioning
confidence: 99%
“…The first involves a family of highly fluorous nonporous coordination polymers. We have shown that the alcohol molecules, which are coordinated to the metal centres, can be removed and reinserted at close to room temperature, despite the lack of porosity in the crystals and the need for changes in metal-carboxylate coordination [1,2]. These transformations occur in a single crystal-to-single crystal manner.…”
mentioning
confidence: 99%